The Future of Web Development: Exploring JavaScript's Role in Web3 and Decentralized Apps - Kapoor, Sonu (International Journal of Scientific Research and Management (IJSRM), 2024)
As the digital landscape evolves, the rise of Web3 and decentralized applications (dApps) is reshaping the future of web development. At the center of this transformation is JavaScript, a programming language that has remained a cornerstone of web development for decades. In the context of Web3, JavaScript continues to play a critical role by enabling seamless interaction with blockchain networks and smart contracts. This article explores the importance of JavaScript in the development of decentralized applications, its integration with blockchain technologies, and its continued adaptability in the ever-growing Web3 ecosystem. From popular libraries like Web3.js and Ethers.js to emerging trends such as decentralized finance (DeFi) and NFTs, JavaScript proves to be a versatile tool in the decentralized web revolution. However, the shift to Web3 also presents challenges for JavaScript, including scalability, security, and performance concerns. This article provides a comprehensive overview of JavaScript’s role in the future of web development, offering insights into both its opportunities and limitations in the decentralized era.